Fiber metal composite laminate and preparation method thereof

By using the MWCNT-STF functional layer in the fiber metal composite laminate, the problem of poor impact resistance of fiber metal composite laminate in the prior art is solved, and higher impact resistance, penetration and energy absorption properties are achieved.

CN118578729BActive Publication Date: 2025-03-11CHENGDU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410749350.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-12
Publication Date
2025-03-11
Estimated Expiration
2044-06-12

AI Technical Summary

Technical Problem

The existing fiber metal composite laminate has poor impact resistance and is difficult to meet the needs of lightweight and high strength in the aerospace and transportation industries.

Method used

Using a functional layer combined with multi-walled carbon nanotubes (MWCNT) and shear thickening liquid (STF), the MWCNT-STF is attached to the Kevlar fiber fabric surface or filled in the fiber gap through an ultrasonic impregnation process to form a fiber metal composite layer.

Benefits of technology

The impact resistance, penetration and energy absorption capacity of the fiber metal composite layer is significantly improved, and its protection against local impact is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118578729B_ABST
    Figure CN118578729B_ABST
Patent Text Reader

Abstract

The present invention discloses a fiber metal composite laminate and a preparation method thereof, and belongs to the technical field of preparation of advanced composite materials. The present invention first grinds MWCNT, PEG and SiO2 together to obtain MWCNT-STF, and then fills the MWCNT-STF dilution obtained after dissolving the MWCNT-STF into the gaps between fiber fabrics or attaches to the surface of the fiber fabric through ultrasonic impregnation, thereby increasing the friction between fiber fabric yarns, and then stacks the MWCNT-STF / fiber fabric, aluminum plate and adhesive film, and obtains a fiber metal composite laminate after hot pressing. This fiber metal composite laminate has strong anti-penetration ability, strong energy absorption ability and good impact resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation of advanced composite materials, and in particular relates to a fiber metal composite laminate and a preparation method thereof. Background Art

[0002] FMLs (Fiber Metal Composite Laminates) are made of metal and fiber reinforced composite materials bonded with high-strength adhesives by hot pressing. Due to their excellent puncture resistance, impact resistance and light weight, fiber metal composite laminates are currently widely used in the aerospace and transportation industries. When cars, airplanes and trains are hit by birds, hail or other foreign objects, it will pose a serious threat to their structural safety.

[0003] In recent years, STF (shear thickening fluid), as a non-Newtonian fluid, has attracted more and more attention due to its unique shear thickening properties. Under low shear stress, STF has a relatively small viscosity. When the external shear stress reaches the critical shear stress of STF, the viscosity of STF will increase sharply, showing a reversible transformation from fluid-like to solid-like. As an energy-absorbing material, STF can be added to aramid fabrics to improve their impact resistance and be made into bulletproof vests. Kevlar fiber has the performance characteristics of high strength, high modulus and low density. It is a widely used protective material, but it takes dozens of layers to achieve a good protective effect.

[0004] In the past few decades, researchers have developed a series of aramid fiber fabrics to replace traditional bulletproof vests. These fabrics are made of high-strength, high-modulus, low-density high-performance fibers. Kevlar fiber fabric is one of the most widely used materials in bulletproof vests. The fabric is light and tough, but it takes dozens of layers to achieve a good protective effect, which makes the protective equipment bulky and inconvenient to wear.

[0005] As people's requirements for the lightweight and strength of FMLs become higher and higher, it is urgent for us to carry out in-depth research on improving the impact resistance of FMLs. Summary of the invention

[0006] In view of the above-mentioned prior art, the present invention discloses a fiber metal composite laminate to solve the technical problem of poor impact resistance of the fiber metal composite laminate in the prior art.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is: to provide a fiber metal composite laminate, which includes a plurality of aluminum plates, a functional layer is sandwiched between each two aluminum plates, and the functional layer is formed by stacking a plurality of layers of MWCNT-STF / fiber fabric and a film; the MWCNT-STF / fiber fabric is prepared by the following steps:

[0008] S1: PEG, MWCNT and SiO2 were mixed and ground to obtain MWCNT-STF;

[0009] S2: dissolving MWCNT-STF in a solvent to obtain a MWCNT-STF dilution solution;

[0010] S3: placing the fiber fabric in a MWCNT-STF dilution solution and ultrasonicating it, then taking out the fiber fabric and drying it.

[0011] Based on the above technical solution, the present invention can also make the following improvements.

[0012] Furthermore, the fiber metal composite laminate has 3 layers of aluminum plates, and the functional layer has 1 to 5 layers of MWCNT-STF / fiber fabrics.

[0013] Furthermore, in step S1, the mass ratio of PEG, MWCNT and SiO2 is: 27-29: 0.2: 70.8-72.8; and the grinding time is 8-12 h.

[0014] Furthermore, in step S1, the mass ratio of PEG, MWCNT and SiO2 is: 28:0.2:71.8; and the grinding time is 10 h.

[0015] Furthermore, in step S2, the solvent is anhydrous ethanol; and the concentration of the MWCNT-STF dilution solution is 30-35 wt %.

[0016] Furthermore, in step S3, the fiber fabric is Kevlar fiber fabric; the ultrasonic time is 0.5 to 1 hour, and the ultrasonic frequency is 35 to 45 KHz.

[0017] Furthermore, in step S3, the drying temperature is 60-80° C., and the drying time is 7-8 hours.

[0018] The present invention also discloses a method for preparing a fiber metal composite laminate, which comprises the following steps:

[0019] (1) Cross-stacking the required amount of MWCNT-STF / fiber fabric and film to form a fiber layer;

[0020] (2) Cross-stack the required amount of surface-treated aluminum plates and fiber layers to form a preliminary sample; the bottom and top layers of the preliminary sample are aluminum plates, and the fiber layers in contact with the aluminum plates are adhesive films;

[0021] (3) The initial sample is hot pressed to obtain the product.

[0022] Furthermore, the surface treatment method of the aluminum plate is: first clean with acetone, then soak in 0.1mol / L NaOH solution and 0.1mol / L HCl solution for 10min and 1h respectively, then put into 0.1mol / L nitric acid solution and 0.1mol / L phosphoric acid solution for deoxidation and anodization respectively, then clean with alcohol, and finally dry at 80°C for 2h.

[0023] Furthermore, the hot pressing temperature is 140-150° C., the hot pressing pressure is 0.3-0.4 MPa, and the hot pressing time is 1.8-2.2 h.

[0024] The beneficial effects of the present invention are:

[0025] 1. The preparation method of the present invention is simple and low in cost.

[0026] 2. The present invention modifies STF by adding MWCNT, and attaches MWCNT-STF to the surface of Kevlar fiber fabric or fills it in the gaps of Kevlar fiber fabric through ultrasonic impregnation process, which can improve the friction between fabric yarns and thus improve the impact resistance of fiber metal composite laminates.

[0027] 3. The mass ratio of PEG, MWCNT and SiO2 in the MWCNT-STF of the present invention is 29-31:0.2:68.8-70.8. The MWCNT-STF with this mass ratio has the best shear thickening effect, which can significantly enhance the impact resistance of the fabric, thereby improving the impact resistance of the fiber metal composite laminate.

[0028] 4. The concentration of the MWCNT-STF dilution in the present invention is 30-35 wt %. The MWCNT-STF at this concentration has the best adhesion effect on the Kevlar fiber fabric, thereby increasing the friction between the fabric yarns.

[0029] 5. The fiber metal composite laminate prepared by the present invention has strong penetration resistance, strong energy absorption capacity and good impact resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is the SEM image of the MWCNT-STF prepared in Example 1;

[0031] Figure 2 is the SEM image of the STF prepared in Comparative Example 2;

[0032] Figure 3 is a SEM image of the MWCNT-STF / Kevlar fiber fabric prepared in Example 1;

[0033] Figure 4 This is the SEM image of the Kevlar fiber fabric in Comparative Example 1;

[0034] Figure 5 is a SEM image of the MWCNT-STF / Kevlar fiber fabric prepared in Comparative Example 5;

[0035] Figure 6 is a SEM image of the MWCNT-STF / Kevlar fiber fabric prepared in Comparative Example 6;

[0036] Figure 7 Critical shear rate diagram of the MWCNT-STF sample or STF sample prepared in Example 1, Comparative Example 2 and Comparative Example 3;

[0037] Figure 8 The peak viscosity graphs of the MWCNT-STF samples or STF samples prepared in Example 1, Comparative Example 2 and Comparative Example 3;

[0038] Fig. 9 The morphology of the sample during the yarn pull-out test of MWCNT-STF / Kevlar fiber fabric. DETAILED DESCRIPTION

[0039] SiO2 was purchased from Shanghai Maoguo Nano Technology Co., Ltd. with an average particle size of 350 nm and a purity greater than 99.5%; aluminum plate (2024T3), polyethylene glycol 200 (PEG 200) and anhydrous ethanol with a purity of 99.7% were purchased from Chengdu Cologne Co., Ltd.; multi-walled carbon nanotubes (MWCNT) were purchased from Shenzhen Suiheng Graphite Technology Co., Ltd., Kevlar fiber was purchased from Yixing Zhongfu Carbon Fiber Products Co., Ltd., and polyethersulfone film was purchased from Suzhou Huiyang Adhesive Products Co., Ltd.

[0040] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.

[0041] Example 1

[0042] A fiber metal composite laminate, comprising three layers of aluminum plates, wherein a functional layer is sandwiched between every two layers of aluminum plates, and the functional layer is formed by stacking a layer of MWCNT-STF / Kevlar fiber fabric and two layers of adhesive film; wherein the MWCNT-STF / Kevlar fiber fabric is prepared by the following steps:

[0043] S1: 28 g PEG200, 0.2 g MWCNT and 71.8 g SiO2 were put into a ball mill and mixed and ground for 10 h to obtain MWCNT-STF;

[0044] S2: dissolving MWCNT-STF in anhydrous ethanol to obtain a MWCNT-STF dilution solution with a concentration of 33.3 wt %;

[0045] S3: Put the Kevlar fiber fabric into the MWCNT-STF dilution solution and ultrasonicate for 0.5h at an ultrasonic frequency of 35KHz, then take out the Kevlar fiber fabric and put it into a vacuum drying oven for drying at a drying temperature of 80°C for 8h to obtain the MWCNT-STF / Kevlar fiber fabric.

[0046] A fiber metal composite laminate is prepared by the following method:

[0047] (1) First, clean the aluminum plate with acetone, then soak it in a 0.1 mol / L NaOH solution at 50°C for 10 min, then soak it in a 0.1 mol / L HCl solution for 1 h, then deoxidize and anodize it in a 0.1 mol / L nitric acid solution and a 0.1 mol / L phosphoric acid solution, then clean it with alcohol, and finally dry it at 80°C for 2 h;

[0048] (2) The surface-treated aluminum plate and the fiber layer are stacked in the form of three layers of aluminum plates with two fiber layers sandwiched in the middle. The fiber layer is one layer of MWCNT-STF / Kevlar fiber fabric. The fiber layer and the aluminum plate are bonded by a polyethersulfone adhesive film. The stack is then placed in a mold and hot-pressed in a hot press for 2 hours. The pressure is set to 0.35 MPa and the hot-pressing temperature is 145°C. The product is then cooled and demolded.

[0049] Example 2

[0050] A fiber metal composite laminate, comprising three layers of aluminum plates, a functional layer is sandwiched between every two layers of aluminum plates, and the functional layer is stacked by two layers of MWCNT-STF / Kevlar fiber fabrics and three layers of adhesive films; wherein the MWCNT-STF / Kevlar fiber fabric is prepared by the following steps:

[0051] S1: 28 g PEG200, 0.2 g MWCNT and 71.8 g SiO2 were placed in a ball mill and mixed and ground for 12 h to obtain MWCNT-STF;

[0052] S2: dissolving MWCNT-STF in anhydrous ethanol to obtain a MWCNT-STF dilution solution with a concentration of 35 wt%;

[0053] S3: Put the Kevlar fiber fabric into the MWCNT-STF dilution solution and ultrasonicate for 1 hour at an ultrasonic frequency of 35 KHz, then take out the Kevlar fiber fabric and put it into a vacuum drying oven for drying at a drying temperature of 60°C and a drying time of 7 hours to obtain the MWCNT-STF / Kevlar fiber fabric.

[0054] A fiber metal composite laminate is prepared by the following method:

[0055] (1) First, clean the aluminum plate with acetone, then soak it in a 0.1 mol / L NaOH solution at 50°C for 10 min, then soak it in a 0.1 mol / L HCl solution for 1 h, then deoxidize and anodize it in a 0.1 mol / L nitric acid solution and a 0.1 mol / L phosphoric acid solution, then clean it with alcohol, and finally dry it at 80°C for 2 h;

[0056] (2) The surface-treated aluminum plate and the fiber layer are stacked in the form of three layers of aluminum plates with two fiber layers sandwiched in the middle. The fiber layer is two layers of MWCNT-STF / Kevlar fiber fabric. The MWCNT-STF / Kevlar fiber fabric and the fiber layer and the aluminum plate are bonded by polyethersulfone adhesive film. Then the stack is placed in a mold and hot-pressed in a hot press for 2.2 hours. The pressure is set to 0.4 MPa and the hot-pressing temperature is 150°C. After cooling and demolding, the product is obtained.

[0057] Example 3

[0058] A fiber metal composite laminate, comprising three layers of aluminum plates, a functional layer is sandwiched between every two layers of aluminum plates, and the functional layer is stacked by three layers of MWCNT-STF / Kevlar fiber fabrics and four layers of adhesive films; wherein the MWCNT-STF / Kevlar fiber fabric is prepared by the following steps:

[0059] S1: 29 g PEG200, 0.2 g MWCNT and 70.8 g SiO2 were placed in a ball mill and mixed and ground for 10 h to obtain MWCNT-STF;

[0060] S2: dissolving MWCNT-STF in anhydrous ethanol to obtain a MWCNT-STF dilution solution with a concentration of 35 wt%;

[0061] S3: Put the Kevlar fiber fabric into the MWCNT-STF dilution solution and ultrasonicate for 1 hour at an ultrasonic frequency of 40 KHz, then take out the Kevlar fiber fabric and put it into a vacuum drying oven for drying at a drying temperature of 70°C and a drying time of 7.5 hours to obtain the MWCNT-STF / Kevlar fiber fabric.

[0062] A fiber metal composite laminate is prepared by the following method:

[0063] (1) First, clean the aluminum plate with acetone, then soak it in a 0.1 mol / L NaOH solution at 50°C for 10 min, then soak it in a 0.1 mol / L HCl solution for 1 h, then deoxidize and anodize it in a 0.1 mol / L nitric acid solution and a 0.1 mol / L phosphoric acid solution, then clean it with alcohol, and finally dry it at 80°C for 2 h;

[0064] (2) The surface-treated aluminum plate and the fiber layer are stacked in the form of three layers of aluminum plates with two fiber layers sandwiched in the middle. The fiber layer is three layers of MWCNT-STF / Kevlar fiber fabric. The MWCNT-STF / Kevlar fiber fabrics and the fiber layer and the aluminum plate are bonded by polyethersulfone adhesive film. Then the stack is placed in a mold and hot-pressed in a hot press for 2 hours. The pressure is set to 0.35 MPa and the hot-pressing temperature is 145°C. After cooling and demolding, the product is obtained.

[0065] Example 4

[0066] A fiber metal composite laminate, comprising three layers of aluminum plates, wherein a functional layer is sandwiched between every two layers of aluminum plates, and the functional layer is formed by stacking a layer of MWCNT-STF / Kevlar fiber fabric and two layers of adhesive film; wherein the MWCNT-STF / Kevlar fiber fabric is prepared by the following steps:

[0067] S1: 27 g PEG200, 0.2 g MWCNT and 72.8 g SiO2 were put into a ball mill and mixed and ground for 8 h to obtain MWCNT-STF;

[0068] S2: dissolving MWCNT-STF in anhydrous ethanol to obtain a MWCNT-STF dilution solution with a concentration of 32 wt%;

[0069] S3: Put the Kevlar fiber fabric into the MWCNT-STF dilution solution and ultrasonicate for 0.5h at an ultrasonic frequency of 45KHz, then take out the Kevlar fiber fabric and put it into a vacuum drying oven for drying at a drying temperature of 80°C for 8h to obtain the MWCNT-STF / Kevlar fiber fabric.

[0070] A fiber metal composite laminate is prepared by the following method:

[0071] (1) First, clean the aluminum plate with acetone, then soak it in a 0.1 mol / L NaOH solution at 50°C for 10 min, then soak it in a 0.1 mol / L HCl solution for 1 h, then deoxidize and anodize it in a 0.1 mol / L nitric acid solution and a 0.1 mol / L phosphoric acid solution, then clean it with alcohol, and finally dry it at 80°C for 2 h;

[0072] (2) The surface-treated aluminum plate and the fiber layer are stacked in the form of three layers of aluminum plates with two fiber layers sandwiched in the middle. The fiber layer is one layer of MWCNT-STF / Kevlar fiber fabric. The fiber layer and the aluminum plate are bonded by a polyethersulfone adhesive film. The stack is then placed in a mold and hot-pressed in a hot press for 1.8 hours. The pressure is set to 0.3 MPa and the hot-pressing temperature is 140°C. The product is then cooled and demolded.

[0073] Comparative Example 1

[0074] A fiber metal composite laminate comprises three layers of aluminum plates, a functional layer is sandwiched between every two layers of aluminum plates, and the functional layer is formed by stacking a layer of Kevlar fiber fabric and two layers of adhesive film.

[0075] A fiber metal composite laminate is prepared by the following method:

[0076] (1) First, clean the aluminum plate with acetone, then soak it in a 0.1 mol / L NaOH solution at 50°C for 10 min, then soak it in a 0.1 mol / L HCl solution for 1 h, then deoxidize and anodize it in a 0.1 mol / L nitric acid solution and a 0.1 mol / L phosphoric acid solution, then clean it with alcohol, and finally dry it at 80°C for 2 h;

[0077] (2) The surface-treated aluminum plate and the fiber layer are stacked in the form of three layers of aluminum plates with two fiber layers sandwiched in the middle. The fiber layer is a layer of Kevlar fiber fabric. The fiber layer and the aluminum plate are bonded by a polyethersulfone adhesive film. The stack is then placed in a mold and hot-pressed in a hot press for 2 hours. The pressure is set to 0.35 MPa and the hot-pressing temperature is 145°C. The product is then cooled and demolded.

[0078] Comparative Example 2

[0079] A fiber metal composite laminate, comprising three layers of aluminum plates, a functional layer is sandwiched between every two layers of aluminum plates, and the functional layer is formed by stacking a layer of MWCNT-STF / Kevlar fiber fabric and two layers of adhesive film; wherein the STF / Kevlar fiber fabric is prepared by the following steps:

[0080] S1: 28g PEG200 and 71.8g SiO2 were placed in a ball mill and mixed and ground for 10h to obtain STF.

[0081] S2: dissolving STF in anhydrous ethanol to obtain a STF dilution solution with a concentration of 33.3 wt %;

[0082] S3: Put the Kevlar fiber fabric into STF dilution solution and perform ultrasound for 0.5 h at an ultrasound frequency of 35 KHz. Then take out the Kevlar fiber fabric and put it into a vacuum drying oven for drying at a drying temperature of 80° C. for 8 h to obtain STF / Kevlar fiber fabric.

[0083] A fiber metal composite laminate is prepared by the following method:

[0084] (1) First, clean the aluminum plate with acetone, then soak it in a 0.1 mol / L NaOH solution at 50°C for 10 min, then soak it in a 0.1 mol / L HCl solution for 1 h, then deoxidize and anodize it in a 0.1 mol / L nitric acid solution and a 0.1 mol / L phosphoric acid solution, then clean it with alcohol, and finally dry it at 80°C for 2 h;

[0085] (2) The surface-treated aluminum plate and the fiber layer are stacked in the form of three layers of aluminum plates with two fiber layers sandwiched in the middle. The fiber layer is a layer of STF / Kevlar fiber fabric. The fiber layer and the aluminum plate are bonded by a polyethersulfone adhesive film. The stack is then placed in a mold and hot-pressed in a hot press for 2 hours. The pressure is set to 0.35 MPa and the hot-pressing temperature is 145°C. The product is then cooled and demolded.

[0086] Comparative Example 3

[0087] A fiber metal composite laminate, comprising three layers of aluminum plates, wherein a functional layer is sandwiched between every two layers of aluminum plates, and the functional layer is formed by stacking a layer of MWCNT-STF / Kevlar fiber fabric and two layers of adhesive film; wherein the MWCNT-STF / Kevlar fiber fabric is prepared by the following steps:

[0088] S1: 28 g PEG200, 0.1 g MWCNT and 71.8 g SiO2 were put into a ball mill and mixed and ground for 10 h to obtain MWCNT-STF;

[0089] S2: dissolving MWCNT-STF in anhydrous ethanol to obtain a MWCNT-STF dilution solution with a concentration of 33.3 wt %;

[0090] S3: Put the Kevlar fiber fabric into the MWCNT-STF dilution solution and ultrasonicate for 0.5h at an ultrasonic frequency of 35KHz, then take out the Kevlar fiber fabric and put it into a vacuum drying oven for drying at a drying temperature of 80°C for 8h to obtain the MWCNT-STF / Kevlar fiber fabric.

[0091] A fiber metal composite laminate is prepared by the following method:

[0092] (1) First, clean the aluminum plate with acetone, then soak it in a 0.1 mol / L NaOH solution at 50°C for 10 min, then soak it in a 0.1 mol / L HCl solution for 1 h, then deoxidize and anodize it in a 0.1 mol / L nitric acid solution and a 0.1 mol / L phosphoric acid solution, then clean it with alcohol, and finally dry it at 80°C for 2 h;

[0093] (2) The surface-treated aluminum plate and the fiber layer are stacked in the form of three layers of aluminum plates with two fiber layers sandwiched in the middle. The fiber layer is one layer of MWCNT-STF / Kevlar fiber fabric. The fiber layer and the aluminum plate are bonded by a polyethersulfone adhesive film. The stack is then placed in a mold and hot-pressed in a hot press for 2 hours. The pressure is set to 0.35 MPa and the hot-pressing temperature is 145°C. The product is then cooled and demolded.

[0094] Comparative Example 4

[0095] 28 g PEG200, 1 g MWCNT and 71.8 g SiO2 were put into a ball mill. After mixing and grinding for 10 h, the sample was severely agglomerated and could not be used.

[0096] Comparative Example 5

[0097] A fiber metal composite laminate, comprising three layers of aluminum plates, wherein a functional layer is sandwiched between every two layers of aluminum plates, and the functional layer is formed by stacking a layer of MWCNT-STF / Kevlar fiber fabric and two layers of adhesive film; wherein the MWCNT-STF / Kevlar fiber fabric is prepared by the following steps:

[0098] S1: 28 g PEG200, 0.2 g MWCNT and 71.8 g SiO2 were put into a ball mill and mixed and ground for 10 h to obtain MWCNT-STF;

[0099] S2: dissolving MWCNT-STF in anhydrous ethanol to obtain a MWCNT-STF dilution solution with a concentration of 20 wt%;

[0100] S3: Put the Kevlar fiber fabric into the MWCNT-STF dilution solution and ultrasonicate for 0.5h at an ultrasonic frequency of 35KHz, then take out the Kevlar fiber fabric and put it into a vacuum drying oven for drying at a drying temperature of 80°C for 8h to obtain the MWCNT-STF / Kevlar fiber fabric.

[0101] A fiber metal composite laminate is prepared by the following method:

[0102] (1) First, clean the aluminum plate with acetone, then soak it in a 0.1 mol / L NaOH solution at 50°C for 10 min, then soak it in a 0.1 mol / L HCl solution for 1 h, then deoxidize and anodize it in a 0.1 mol / L nitric acid solution and a 0.1 mol / L phosphoric acid solution, then clean it with alcohol, and finally dry it at 80°C for 2 h;

[0103] (2) The surface-treated aluminum plate and the fiber layer are stacked in the form of three layers of aluminum plates with two fiber layers sandwiched in the middle. The fiber layer is one layer of MWCNT-STF / Kevlar fiber fabric. The fiber layer and the aluminum plate are bonded by a polyethersulfone adhesive film. The stack is then placed in a mold and hot-pressed in a hot press for 2 hours. The pressure is set to 0.35 MPa and the hot-pressing temperature is 145°C. The product is then cooled and demolded.

[0104] Comparative Example 6

[0105] A fiber metal composite laminate, comprising three layers of aluminum plates, wherein a functional layer is sandwiched between every two layers of aluminum plates, and the functional layer is formed by stacking a layer of MWCNT-STF / Kevlar fiber fabric and two layers of adhesive film; wherein the MWCNT-STF / Kevlar fiber fabric is prepared by the following steps:

[0106] S1: 28 g PEG200, 0.2 g MWCNT and 71.8 g SiO2 were put into a ball mill and mixed and ground for 10 h to obtain MWCNT-STF;

[0107] S2: dissolving MWCNT-STF in anhydrous ethanol to obtain a MWCNT-STF dilution solution with a concentration of 33.3 wt %;

[0108] S3: Put the Kevlar fiber fabric into the MWCNT-STF dilution solution and ultrasonicate for 0.5h at an ultrasonic frequency of 35KHz, then take out the Kevlar fiber fabric and put it into a vacuum drying oven for drying at a drying temperature of 80°C for 8h to obtain the MWCNT-STF / Kevlar fiber fabric.

[0109] A fiber metal composite laminate is prepared by the following method:

[0110] (1) First, clean the aluminum plate with acetone, then soak it in a 0.1 mol / L NaOH solution at 50°C for 10 min, then soak it in a 0.1 mol / L HCl solution for 1 h, then deoxidize and anodize it in a 0.1 mol / L nitric acid solution and a 0.1 mol / L phosphoric acid solution, then clean it with alcohol, and finally dry it at 80°C for 2 h;

[0111] (2) The surface-treated aluminum plate and the fiber layer are stacked in the form of three layers of aluminum plates with two fiber layers sandwiched in the middle. The fiber layer is one layer of MWCNT-STF / Kevlar fiber fabric. The fiber layer and the aluminum plate are bonded by a polyethersulfone adhesive film. The stack is then placed in a mold and hot-pressed in a hot press for 2 hours. The pressure is set to 0.35 MPa and the hot-pressing temperature is 145°C. The product is then cooled and demolded.

[0112] Experimental example

[0113] The fiber metal composite laminates produced in the embodiments of the present invention have similar performances, and the performances of related products are described below.

[0114] 1. Structural test

[0115] The MWCNT-STF samples and STF samples prepared in Example 1 and Comparative Example 2 were photographed using a scanning electron microscope (SEM, Tescan MIRA30, Czech Republic). Before photographing the STF samples, the STF samples needed to be diluted with alcohol and dried. A suitable amount of the treated samples were placed on the conductive adhesive, and the distribution of SiO2 and MWCNT in the samples was observed after gold spraying. The results are shown in FIG. Figures 1-2 As shown. Figure 1 It can be seen that the SiO2 particles are regular spherical and are evenly distributed by MWCNTs.

[0116] The morphology of the fiber fabric samples in Example 1, Comparative Example 1, Comparative Example 5 and Comparative Example 6 was photographed using a scanning electron microscope (SEM, Tescan MIRA30, Czech Republic). When photographing the SEM morphology of the fiber fabric, the fiber fabric was first cut into a suitable size and attached to the conductive adhesive. Since the fiber fabric is not conductive, it is necessary to use a sputtering coating machine (Oxford Quorum SC7620, England) to spray gold at 10 mA for 45 seconds. The shooting acceleration voltage was set to 3 kV, and a suitable scale was selected to save the morphology picture. The results are shown in FIG. Figures 3 to 6As shown, it can be seen that the surface of the MWCNT-STF / Kevlar fiber fabric in the embodiment is significantly rougher than that of the Kevlar fiber fabric in Comparative Example 1. This is because when the Kevlar fiber fabric is impregnated with MWCNT-STF, it is subjected to ultrasonic oscillation treatment, making the Kevlar fiber fabric more fluffy, and the gaps between the yarns of the Kevlar fiber fabric are filled with MWCNT-STF. It can also be seen that the MWCNT-STF in the embodiment has the best filling effect between the gaps in the Kevlar fiber fabric and the best adhesion effect on the surface of the Kevlar fiber fabric, which can increase the friction between the fabric yarns, thereby improving the impact resistance of the fiber fabric.

[0117] 2. Rheological study

[0118] The viscosity-shear rate data of the MWCNT-STF samples or STF samples prepared in Example 1, Comparative Example 2 and Comparative Example 3 were measured using a modular intelligent advanced rotational rheometer MCR302 (Anton Paar Germany). The rheometer consists of a base plate and a rotor. The rotor is a parallel circular plate rotor with a diameter of 50 mm. The gap between the base plate and the end face of the rotor is set to 1 mm. The temperature is set to 25°C. The shear rate range is set to 0.01 to 1000 s -1 , take an appropriate amount of sample and place it on the rheometer for preliminary test. After the preliminary test, clean the sample and start the formal test. After each sample test, wipe the bottom plate and rotor of the rheometer clean to avoid affecting the test results. The shear rate-viscosity data is obtained through the rheometer. The experimental results are as follows Figure 7 and Figure 8 As shown in the figure, it can be seen that adding MWCNT to STF will reduce the critical shear rate of the STF sample and increase the peak viscosity, thereby improving the shear thickening effect. The MWCNT-STF sample in the embodiment has a better effect.

[0119] 3. Yarn pull-out test

[0120] To investigate the adhesion effect of MWCNT-STF on Kevlar fiber fabric, one end of the MWCNT-STF / Kevlar fiber fabric prepared in Example 1, Comparative Example 5 and Comparative Example 6 was cut off by 80 mm and one fiber at the central axis was retained. The other end of the fiber at the central axis was cut off. The morphology of the sample is shown in FIG. Fig. 9 The prepared sample was clamped on a universal testing machine. The clamping distance at both ends of the sample was 40 mm. The axial fiber of the sample was pulled out at a pulling speed of 20 mm / min, 200 mm / min and 500 mm / min, respectively. The results are shown in Table 1.

[0121] Table 1

[0122]

[0123] It can be seen from Table 1 that at the same pulling speed, the pulling force required in the embodiment is significantly greater than that in the comparative example, indicating that the MWCNT-STF dilution solution with a concentration of 30-35wt% has the best adhesion effect on the Kevlar fiber fabric, thereby significantly improving the friction between the fabric yarns.

[0124] 4. Quasi-static penetration test

[0125] Quasi-static penetration tests were performed on the fiber metal composite laminates prepared in the examples and comparative examples. The fiber metal composite laminates were fixed to an ASTM D7136 fixture with bolts. The fixture was provided with positioning pins to position the fiber metal composite laminates. The bottom opening was a 50 mm diameter circular hole. A hemispherical indenter with a diameter of 10 mm was installed on a universal testing machine. The specimens were loaded at a loading rate of 2 mm / min. The test results are shown in Table 2.

[0126] Table 2

[0127]

[0128]

[0129] It can be seen from the table that the energy required to penetrate the fiber metal composite laminate increases with the increase in the number of fiber layers. For FMLs in the same stacking mode, the fiber metal composite laminate treated with MWCNT-STF requires greater penetration energy. In the embodiment, the MWCNT-STF dilution with a concentration of 30-35wt% is attached and filled between Kevlar fiber fabrics, and the attachment and filling effect is the best. The friction between the fabric yarns is higher, and the fabric has strong anti-penetration ability, so that the fiber metal composite laminate has strong energy absorption ability and strong anti-penetration ability.

[0130] 5. Drop hammer impact test

[0131] With reference to ASTM D7136 standard, the test was carried out on a drop hammer tester equipped with a secondary impact protection device. The contact force during the impact process was obtained by a pressure sensor installed at the other end of the impact head, and the displacement data and impact energy of the impact head were calculated by a software program. The energy absorption data of the specimen during the impact process was obtained by integrating the area of ​​the force-displacement curve. All tests were performed using a hemispherical impact head with a diameter of 10 mm. The total mass of the impact head and the counterweight block was 23.948 kg, and the impact energy of the drop hammer tester was determined by the total mass of the impact head and the counterweight block. The impact energy of the drop hammer impact test was the quasi-static penetration energy of the specimen × 2 as the impact energy of the impact test. The energy absorption was calculated based on the area of ​​the force-displacement curve during the low-speed impact process. The test results are shown in Table 3.

[0132] Table 3

[0133]

[0134] As can be seen from the table, the absorbed energy increases with the increase in the number of fiber layers. The fiber metal composite laminates under the same stacking method, after being treated with MWCNT-STF, absorb more energy because the shear thickening mechanism of MWCNT-STF is triggered during the low-speed impact process, which causes the viscosity of MWCNT-STF to increase rapidly, the friction between the yarns increases, and the resistance during the impact of the collision head is increased. In the embodiment, the MWCNT-STF dilution with a concentration of 30-35wt% is attached and filled between the Kevlar fiber fabrics, and the attachment and filling effect is the best, the friction between the fabric yarns is higher, and the impact resistance of the fiber metal composite laminate is greatly improved.

[0135] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.

Claims

1. A fiber metal composite laminate, characterized in that: The fiber metal composite laminate comprises a plurality of aluminum plates, a functional layer is sandwiched between every two aluminum plates, and the functional layer is formed by stacking a plurality of MWCNT-STF / fiber fabrics and adhesive films; the MWCNT-STF / fiber fabrics are prepared by the following steps: S1: PEG, MWCNT and SiO2 are mixed and ground to obtain MWCNT-STF; the mass ratio of PEG, MWCNT and SiO2 is: 27-29: 0.2: 70.8-72.8; the grinding time is 10-12h; S2: dissolving the MWCNT-STF in a solvent to obtain a MWCNT-STF dilution solution; the concentration of the MWCNT-STF dilution solution is 30-35 wt %; S3: placing the fiber fabric into the MWCNT-STF dilution solution and ultrasonicating it, then taking out the fiber fabric and drying it, to obtain the product; the ultrasonic time is 0.5 to 1 h, and the ultrasonic frequency is 35 to 45 KHz.

2. The fiber metal composite laminate according to claim 1, characterized in that: The fiber metal composite laminate has 3 layers of aluminum plates; the functional layer has 1 to 5 layers of MWCNT-STF / fiber fabrics.

3. The fiber metal composite laminate according to claim 1, characterized in that: The mass ratio of PEG, MWCNT and SiO2 in step S1 is: 28:0.2:71.8; the grinding time is 10h.

4. The fiber metal composite laminate according to claim 1, characterized in that: The solvent in step S2 is anhydrous ethanol.

5. The fiber metal composite laminate according to claim 1, characterized in that: The fiber fabric in step S3 is Kevlar fiber fabric.

6. The fiber metal composite laminate according to claim 1, characterized in that: In step S3, the drying temperature is 60-80° C. and the drying time is 7-8 hours.

7. The method for preparing the fiber metal composite laminate according to any one of claims 1 to 6, characterized in that: It comprises the following steps: (1) Cross-stacking the required amount of MWCNT-STF / fiber fabric and film to form a fiber layer; (2) Cross-stacking the required amount of surface-treated aluminum plates and fiber layers to form a preliminary sample; The bottom and top layers of the initial sample are aluminum plates, and the fiber layer in contact with the aluminum plates is a film; (3) The initial sample is hot pressed to obtain the product.

8. The preparation method according to claim 7, characterized in that: The surface treatment method of the aluminum plate is: first clean it with acetone, then soak it in 0.1mol / L NaOH solution and 0.1mol / L HCl solution for 10min and 1h respectively, then put it in 0.1mol / L nitric acid solution and 0.1mol / L phosphoric acid solution for deoxidation and anodization respectively, then clean it with alcohol, and finally dry it at 80℃ for 2h.

9. The preparation method according to claim 7, characterized in that: The hot pressing temperature is 140-150° C., the hot pressing pressure is 0.3-0.4 MPa, and the hot pressing time is 1.8-2.2 h.

Citation Information

Patent Citations

  • Preparation method of soft and durable anti-penetrating material

    CN107815870A